SCIENTIFIC AND METODICAL APPROACHES TO DEVELOPMENT OF PROJECTS OF LAND MANAGEMENT ONESTABLISHMENT OF COASTAL PROTECTIVE STRIPS - Osypchuk, S. O.; Koshel, A. O. (Землеустрій, кадастр і моніторинг земель, 2012)
Scientific and methodical approaches to development of projects of land management on establishment of coastal protective strips which are based on provisions of operationg standard and legal base and the accounting of ecological and economic requirements of rather ration use of the land lost of water fund are offered.